Bioinspired Modifications of PEEK Implants for Bone Tissue Engineering - Gu, Xinming; Sun, Xiaolin; Sun, Yue; Wang, Jia; Liu, Yiping; Yu, Kaixuan; Wang, Yao; Zhou, Yanmin (Frontiers in Bioengineering and Biotechnology, 2021)
In recent years, polyetheretherketone (PEEK) has been increasingly employed as an implant material in clinical applications. Although PEEK is biocompatible, chemically stable, and radiolucent and has an elastic modulus similar to that of natural bone, it suffers from poor integration with surrounding bone tissue after implantation. To improve the bioactivity of PEEK, numerous strategies for functionalizing the PEEK surface and changing the PEEK structure have been proposed. Inspired by the components, structure, and function of bone tissue, this review discusses strategies to enhance the biocompatibility of PEEK implants and provides direction for fabricating multifunctional implants in the future.